2013
DOI: 10.1016/j.juro.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement Therapy in Patients with Prostate Cancer After Radical Prostatectomy

Abstract: Purpose Testosterone replacement therapy in men with prostate cancer is controversial, with concern that testosterone can stimulate cancer growth. We evaluated the safety and efficacy of testosterone in hypogonadal men with prostate cancer treated with radical prostatectomy. Materials and Methods We performed a review of 103 hypogonadal men with prostate cancer treated with testosterone after prostatectomy (treatment group) and 49 nonhypogonadal men with cancer treated with prostatectomy (reference group). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 25 publications
8
109
0
3
Order By: Relevance
“…[5][6][7][8][9][10][11] An important question is whether these observations are substantial enough to impact the clinical management of hypogonadism in men under active surveillance for low-stage/grade PCa. The evidence specifically pertaining to active surveillance Canadian opinions about testosterone replacement is even more limited, but the results of our survey reveal that 65% of a representative sample of Canadian urologists believe that this practice is safe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11] An important question is whether these observations are substantial enough to impact the clinical management of hypogonadism in men under active surveillance for low-stage/grade PCa. The evidence specifically pertaining to active surveillance Canadian opinions about testosterone replacement is even more limited, but the results of our survey reveal that 65% of a representative sample of Canadian urologists believe that this practice is safe.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate studies that examined a total of 17 men with a history of radical prostatectomy and who were treated with TRT for TDS found no recurrence of cancer. 5,6 A 2013 study by Pastuszak et al examined 152 men who underwent total prostatectomy for PCa, 7 103 hypogonadal men treated with TRT (26 of whom were "highrisk"), and a reference group of 49 non-hypogonadal men. They found an increase in prostate-specific antigen (PSA) in the treatment group, but only four of these men had cancer recurrence, compared to eight in the reference group.…”
Section: Introductionmentioning
confidence: 99%
“…In a newer retrospective review of 103 hypogonadal men after prostatectomy, Pastuszak found that, while TRT may increase PSA, it did not increase the rate of prostate cancer (4 recurrences on TRT, 8 recurrences in reference group) at a median follow-up of 27.5 months. In fact, the study further stratified these men by risk category and found that of the 23 high-risk men (Gleason 8-10 or positive margins or lymph nodes), there were no recurrences while on TRT, suggesting that TRT can be safe regardless of risk [75].…”
Section: Trt On Patients With Prostate Cancermentioning
confidence: 98%
“…Among both groups, all biochemical recurrences were Testosterone deficiency and replacement: Myths and realities seen in men with high-risk features (Gleason score 8 or higher, positive surgical margins or lymph nodes), suggesting that the characteristics of the cancer themselves drive recurrences versus testosterone levels or replacement. 28 In a study of 13 hypogonadal men with untreated prostate cancer undergoing active surveillance, TRT for a median of 30 months was not associated with increased PSA levels or prostate cancer progression. 29 Many healthcare providers hesitate to initiate men on TRT due to the belief that these treatments increase the risk of cardiovascular (CV) events.…”
Section: Introductionmentioning
confidence: 97%